Of course you know what to prove

gof(x) = gof(y) x = y

Since g(f(x)) = g(f(y)) and g is one-one, we have f(x) = f(y). Since f is also 1-1, we have x=y.

2) is nice, I will give you a general hint,try it

General Hint: Draw a few blobs(actually 3, they are the sets). Mark some points in them(they are the elements). Now map points from one blob to another, remembering they conditions in data. Try your best to prove the question wrong. You will see why itbe right. Geometric intuition is your best pal, learn to use him.must